ASPEK PERIZINAN BAGI WIRAUSAHAWAN UMKM KADER PKK PH7 CILEUNGSI, BOGOR, JAWA BARAT - Andi Setiawan; Retno Widowati; Damdam Damiyana; Minggu Minggu; Kania Farida (JURNAL ABDIMAS PLJ, 2021)
An overview of the culinary business licensing for PKK cadres at Puri Harmoni 7 Housing in Cileunyi, Bogor, West Java is a difficult matter, requires no small amount of money, and complicated bureaucracy. This condition causes them to be lazy to take care of licensing. Reluctance and ignorance of the benefits of licensing can cause them to deal with the authorities. This community service is here to provide enlightenment about the ease of taking care of licensing online and its benefits. LP3I Jakarta Polytechnic in collaboration with PT Kinarya Insan Kreatif provides training and counseling. The method of activity is legal socialization through limited face-to-face lectures by complying with the 5 M health protocol. The object of this service is a contemporary food product that comes from cassava. This counseling material includes legal protection and assistance, obtaining a Business Identification Number permit, the establishment of  PT Perseorangan, and halal certificates. The implementation of this activity is carried out through the stages of problem identification, site survey, planning, implementation, and evaluation of activities as well as preparation of reports. The result obtained is knowledge about the importance of licensing, awareness and desire to take care of it in person and onlineKeywords: Counseling, Licensing, Entrepreneurship, MSME, PKK.